Chemical munition dump sites in coastal environments - Missiaen, T., ....-; Henriet, Jean-Pierre, 1945- (Brussels : Federal Office for Scientific, Technical and Cultural Affairs and Federal Ministry of Social Affairs, Public Health and the Environment, 2002)
1.Status assessment 2.Risk assessment 3.Policy
Keywords: Chemische wapens; Waterverontreiniging